Prevalence of smell and taste dysfunction in a cohort of CoVID19 outpatients managed through remote consultation from a large urban teaching hospital in Dublin, Ireland - Colm Kerr; Gerry Hughes; Louise McKenna; Colm Bergin (Elsevier, 2020)
Summary: Background: Coronaviruses are known to precipitate disorders of smell and taste function. With the emerging global coronavirus disease (CoVID19) pandemic due to the severe acute respiratory syndrome coronavirus 2, early reports suggested that smell and taste dysfunction were clinical features of CoVID19. Our study aimed to investigate the prevalence of smell and taste disturbances in a cohort of CoVID19 positive patients who were isolated at home and being medically managed through telephone consultation. Methods: This was a retrospective cross-sectional study conducted at St. James's Hospital Dublin, an urban 850 bed tertiary referral centre. 46 out of 50 CoVID19 positive patients, managed through a telephone clinic from the hospital infectious disease department, were assessed for olfactory and gustatory function loss. Results: The median age of participants was 36.5 years (interquartile range (IQR) 27 - 48) and 19 (41%) were male. The majority (31; 67%) never smoked and 17 (37%) reported co-morbidities. Approximately half of patients reported some degree of smell (22; 48%) or taste (25; 54%) function loss. 13 patients (28%) reported a complete loss of sense of smell, 8 (17%) reported a complete loss of sense of taste and 7 (15%) reported simultaneous total loss of both. The median age of patients with any degree of smell disturbance was significantly lower than patients without (median 30.5 years (IQR 24 - 43.25) versus 41 years (IQR 28.25 - 52.75), p = 0.025). The median age of patients with any degree of taste disturbance was lower than those without, but did not reach statistical significance (median 34 years (IQR 24 - 45) versus 40 years (IQR 27.5 - 52.5) p = 0.174). Conclusion: Smell or taste dysfunction were present in our defined subgroup of patients. Further research is required in different population cohorts to build the evidence base for smell and taste dysfunction as clinical indicators of CoVID19 disease and to assess if these symptoms persist after disease resolution.